2022
DOI: 10.3390/agriculture12050609
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptides Produced by Bacillus mojavensis P1709 as an Efficient Tool to Maintain Postharvest Cherry Tomato Quality and Quantity

Abstract: Because of significant yield losses caused by fungal pathogens, new efficient and environmentally safe methods of pest control are needed, and amphiphilic compounds (biosurfactants) produced by many microbes are considered a good alternative. In the present study, biosurfactants produced by the rhizosphere isolate Bacillus mojavensis P1709 were assessed for their ability to protect postharvest cherry tomatoes from decay and mycotoxin contamination caused by Fusarium oxysporum f. sp. lycopersici. It was demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…A previous study suggested that the LPs from B. subtilis ABS-S14 act as defense-related genes to inhibit pathogen growth (Waewthongrak et al, 2014). Another study produced similar results showing that LPs produced by B. mojavensis P1709 are an effective tool for controlling postharvest decay and mycotoxin contamination in cherry tomatoes (Galitskaya et al, 2022). In conclusion, we report that LPs produced by B. subtilis strain Y17B potentially exert strong antifungal activity against A. alternata, causing ultrastructural damage to the pathogen and reducing the disease intensity of A. alternata on cherry fruit.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study suggested that the LPs from B. subtilis ABS-S14 act as defense-related genes to inhibit pathogen growth (Waewthongrak et al, 2014). Another study produced similar results showing that LPs produced by B. mojavensis P1709 are an effective tool for controlling postharvest decay and mycotoxin contamination in cherry tomatoes (Galitskaya et al, 2022). In conclusion, we report that LPs produced by B. subtilis strain Y17B potentially exert strong antifungal activity against A. alternata, causing ultrastructural damage to the pathogen and reducing the disease intensity of A. alternata on cherry fruit.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have shown that B. mojavensis had inhibitory effects on a variety of pathogens. Galitskaya et al [ 45 ] reported that B. mojavensis P1709 could protect postharvest cherry tomatoes from fungal pathogens, and Bacon et al [ 46 ] reported that Bacillus mojavensis could reduce stalk lesions in maize seedlings. In this study, B. mojavensis BQ-33 had an inhibitory activity on D. glomerata , Botryosphaeria dothidea , Alternaria alternata , Fusarium oxysporum and Phomopsis cauloides .…”
Section: Discussionmentioning
confidence: 99%
“…Because of significant yield losses caused by fungal pathogens, new, efficient, and environmentally safe methods of pest control are needed, hence, amphiphilic compounds or the BSs produced by many microbes are considered a good alternative. Galitskaya et al (2022) reported the use of B. mojavensis P1709-derived lipopeptide BSs against F. oxysporum f. sp. lycopersici affecting the cherry tomato.…”
Section: Use Of Biosurfactants And/or Bs-producing Microorganisms In ...mentioning
confidence: 99%
“… Galitskaya et al (2022) reported the use of B. mojavensis P1709-derived lipopeptide BSs against F. oxysporum f. sp. lycopersici affecting the cherry tomato.…”
Section: Use Of Biosurfactants And/or Bs-producing Microorganisms In ...mentioning
confidence: 99%